EU Influence Beyond Conditionality: Turkey Plus/Minus the EU - TÜRKDOĞAN, SEYYİDE SENA (Routledge Journals, Taylor & Francis Ltd., 2021)
Turkey has deep historical roots with the European Union (EU). The Turkish application to establish an association with then-European Economic Community in 1959 marked the first interaction between the two, and after several attempts Turkey received candidate state status in 1999. The beginning of Turkey’s accession negotiations on October 2005 constituted an important turning point for Turkey’s relations with the EU and Turkey’s socio-political transformation...